Incidencia De La Destreza Listening A Través De Diálogos Y Closed Caption En El Aprendizaje Del Idioma Inglés - Luis Oswaldo Guadalupe Bravo; Enrique Jesús Guambo Yerovi; Luis Alberto Veloz Andrade; Salazar Calderón Edison Hernán; Mancero Orozco Washington Gustavo; Armas Pesantez Paul Rolando (European Scientific Journal, ESJ, 2018)
The objective of the present investigation was to make a diagnosis to the students of second year of baccalaureate parallel "H" of Pedro Vicente Maldonado High School in order to determine that the development of the skill of listening through activities like the dialogue and closed caption and the use of technologies of information and communication, contribute in the listening comprehension and therefore in the English language learning. The difficulty in the listening comprehension was detected because of the student’s low grades in the subject of the English. The research was scientific, quasiexperimental, and bibliographical, the information was collected through the technique of observation with a checklist that allowed the teacher to evaluate the student's performance. Both the activities and the parameters of the collation list were validated and verified by academic peers. The activities were organized in a timeline for their implementation; later the results were tabulated, analyzed, and interpreted, and subjected to the Chi square statistical test for the hypothesis test. Where it was shown that the application of activities with the help of the ICTs of the listening skill benefits the listening comprehension and thus the learning of the English language.